2022
DOI: 10.3389/fendo.2022.904005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Modified Electroconvulsive Therapy on Serum Cortisol, Nesfatin-1, and Pro-inflammatory Cytokine Levels in Elderly Patients With Treatment-Resistant Depression

Abstract: AimModified electroconvulsive therapy (MECT) is an effective strategy for treatment-resistant depression (TRD); however, the mechanism underlying effects of MECT remains unclear. Accumulating evidence suggests that TRD is closely associated with dysfunction of the hypothalamic-pituitary-adrenal (HPA) axis, anorexigenic peptides, and pro-inflammatory cytokines. However, MECT effects on the HPA axis, anorexigenic peptides, and pro-inflammatory cytokines in elderly patients with TRD remain unclear. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Several studies have demonstrated that ECT can lead to a long‐term reduction in peripheral cytokine levels, 18–21 suggesting an anti‐inflammatory effect. However, more recent studies have shown that ECT did not significantly alter the peripheral blood concentrations of the inflammatory mediators in depressed patients 22–24 . In animal models, where electroconvulsive shock (ECS) is used to mimic the human intervention, the effects of ECS on central inflammation have not fully been disentangled either.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that ECT can lead to a long‐term reduction in peripheral cytokine levels, 18–21 suggesting an anti‐inflammatory effect. However, more recent studies have shown that ECT did not significantly alter the peripheral blood concentrations of the inflammatory mediators in depressed patients 22–24 . In animal models, where electroconvulsive shock (ECS) is used to mimic the human intervention, the effects of ECS on central inflammation have not fully been disentangled either.…”
mentioning
confidence: 99%
“…However, more recent studies have shown that ECT did not significantly alter the peripheral blood concentrations of the inflammatory mediators in depressed patients. [22][23][24] In animal models, where electroconvulsive shock (ECS) is used to mimic the human intervention, the effects of ECS on central inflammation have not fully been disentangled either. Some studies have indicated that ECS can lead to astrocyte activation and an increase in inflammatory cytokines in the short term [25][26][27] ; however, these effects are rapid and may be transient.…”
mentioning
confidence: 99%